99mTc radiolabelling of Fe3O4–Au core–shell and Au–Fe3O4 dumbbell-like nanoparticles1. Issue 15 (21st April 2015) - Felber, M.; Alberto, R.
<x xml:space="preserve">Abstract</x> Novel bifunctional coating ligands were synthesized for the radiolabelling of Fe3O4–Au core–shell and Au–Fe3O4 dumbbell-like nanoparticles with the [99mTc(CO)3]+ fragment.